Can sleep affect destination memory? A prospective narrative review - Rathore, Tanisha; Joshi, Gunjan; Verma, Kedarmal (Frontiers in Psychology, 2025)
The destination memory is the ability of individuals to remember to whom the information has been delivered. The memory system is an essential and critical piece of social communication and human social cognition. Previously, research has been done on the relationship between source memory and sleep which are critical and fundamental processes influencing our daily lives. However, this present prospective narrative review sheds light on the idea of beginning new research to understand the relationship between destination memory and sleep. Although no such literature exists that can explain this relationship, this review will try to understand prospective future directions by synthesizing available literature on sleep and the source memory. The present narrative review provides an overview of research executed in the fields of source memory, destination memory, and sleep. Destination memory and source memory are the opposite sides of the same coin. They are a part of the episodic memory system. Research suggests that they share similarities, namely their contextual nature, involvement of the pre-frontal cortex (PFC), and role of the medial temporal lobe (MTL). Studies on the effect of sleep on source memory have indicated that it plays a role in consolidation. This consolidation involves binding the item to its context. Due to the shared characteristics of source and destination memory, it can be suggested that sleep may play a role in influencing destination memory. Understanding this relationship will have implications for enhancing social memory/communication efficacy through sleep hygiene.